Miskonsepsi Proses Berpikir Peserta Didik dengan Pendidik pada Topik Pertidaksamaan - Herdiana, Nanang (Jurnal Inovasi dan Teknologi Pendidikan, 2022)
Misconceptions of students or a wrong understanding of a mathematical concept are often found during learning as above the problem. Therefore, misconceptions are one of the things that must be considered in the world of education. All efforts to improve the quality of education ultimately aim to improve the abilities of students. One of the abilities of students can be seen from the students' understanding of a concept. Misconception is a part of the conceptual framework that is wrong but is considered correct by the learner so that errors occur that appear repeatedly and consistently. Analysis of the thinking process of students on this topic of inequality is carried out in order to obtain a clear picture of the occurrence of misconceptions experienced by students. So that a clear picture of this misconception will be used as a way to prevent misconceptions. The investigation of misconceptions in this study begins with describing the learners' mistakes in the topic of inequality. Continue to trace what misconceptions the learners experienced. So that a clear picture of the misconceptions of students on the topic of inequality is obtained. Based on this description, the researcher will examine with the title "Misconceptions of The Thinking Process of Students with Educators on the Topic of Inequality". The following will be presented the various misconceptions experienced by learners on the topic of inequality found by the researcher: 1) The learner considers that when completing A variable inequality (e.g. x) must always be present on the left or on the left segment; 2) The learner considers that the process of solving the inequality is the same as the equation; 3) The learner considers that when multiplying or dividing the two condiment segments by a negative number the sign of adversity does not need to be changed; 4) The learner assumes that when the form of a fraction is in the form of a fraction, the segment that has a fraction must be multiplied by the KPK from the denominator, and vice versa; 5)The learner assumes that if the absolute value of the sign is omitted it is equal in value